Vasamuseet, detail model - (:unkn) unknown (Chalmers tekniska högskola // Institutionen för arkitektur och samhällsbyggnadsteknik, 2022)
The vasa museum is the most visited Museum in Sweden today. The building is situated on Djurgården, an island in the middle of Stockholm city. There are many museums in the area such as the Nordic museum, Abba museum, and Skansen.
Vasa museum, detail model